The differences in the quality of life of allergic rhinitis and non-symptomatic individuals - Ayu Betty Hutagaol; Indri Adriztina (PERHATI-KL, 2021)
ABSTRACTBackground: Allergic rhinitis is a chronic inflammatory disorder of the nose that occurs as an IgE-mediated reaction. Classical symptoms of allergic rhinitis are sneezing, nasal congestion, nasal itching and rhinorrhea. The effects of allergic rhinitis can have an impact on daily activities that affect the quality of life of sufferers. Purpose: To determine the differences between the quality of life of allergic rhinitis sufferers and non-symptomatic subjects in the Faculty of Medicine, University of North Sumatra batch 2017. Methods: This was an observational study with a cross-sectional design. The research sample was obtained by total sampling technique and used two questionnaires, Score for Allergic Rhinitis (SFAR) to assess allergic rhinitis, and 36-Item Short Form Health Survey (SF 36) to assess the quality of life of the research subjects, which were students of the Faculty of Medicine, University of North Sumatra, of the year 2017. Result: Among 213 students from the Faculty of Medicine, University of Sumatera Utara of the year 2017, there were 112 allergic rhinitis sufferers and 101 non-symptomatic students. The median quality of life score for allergic rhinitis sufferers was 74, while the median score of quality of life for non-symptomatic students was 78. Using Man Whitney test, the result obtained p value <0.05 (p = 0.044). Conclusion: There was a significant difference between the quality of life of students with allergic rhinitis and non-symptomatic individuals.Keywords: allergic rhinitis, quality of life, SFAR, SF-36ABSTRAKLatar belakang: Rinitis alergi merupakan inflamasi yang terjadi pada hidung akibat adanya reaksi alergi yang diperantarai oleh IgE. Gejala rinitis alergi berupa bersin-bersin, hidung tersumbat, serta hidung gatal dan rinore. Gejala rinitis alergi dapat berdampak pada aktivitas sehari-hari sehingga mempengaruhi kualitas hidup penderitanya. Tujuan: Mengetahui perbedaan kualitas hidup penderita dan bukan penderita rinitis alergi pada mahasiswa Fakultas Kedokteran Universitas Sumatera Utara, angkatan 2017. Metode: Penelitian ini merupakan jenis penelitian analitik observasional dengan rancangan cross-sectional. Sampel penelitian ditentukan dengan teknik total sampling dan menggunakan dua buah kuesioner yaitu Score for Allergic Rhinitis (SFAR) untuk menilai rinitis alergi dan 36-Item Short Form Health Survey (SF-36) untuk menilai kualitas hidup. Subjek penelitian adalah mahasiswa Fakultas Kedokteran Universitas Sumatera Utara angkatan 2017. Hasil: Dari 213 mahasiswa Fakultas Kedokteran Universitas Sumatera Utara angkatan 2017, didapati 112 penderita rinitis alergi dan 101 bukan penderita rinitis alergi. Skor median kualitas hidup penderita rinitis alergi adalah 74 sedangkan skor median kualitas hidup mahasiswa bukan penderita rinitis alergi adalah 78. Dengan uji Man Whitney diperoleh hasil p value <0,05 (p=0,044). Kesimpulan: Penelitian ini menunjukkan adanya perbedaan signifikan antara kualitas hidup penderita rinitis alergi dan bukan penderita rinitis alergi.Kata kunci: rinitis alergi, kualitas hidup, SFAR, SF 36